Free Radical Scavenging Effect of Donepezil as the Possible Contribution to its Memory Enhancing Activity in Mice - Umukoro, S.; Adewole, F. A.; Eduviere, A. T.; Aderibigbe, A. O.; Onwuchekwa, C. (Drug Research, 2014)
Donepezil (DP) is the major drug currently used for enhancing memory function in patients with Alzheimer’s disease (AD), an action ascribed to the elevation of central cholinergic neurotransmission. However, there are indications that DP may protect neurons against injury through the prevention of free radical-mediated neuroinflammation that has been implicated in the pathology of AD. Thus, this study was carried out to examine the effect of DP on memory impairment and on biomarkers of oxidative stress induced by scopolamine (SC) and lipopolysaccharide (LP) in mice.Mice were treated with DP (0.5–4 mg/kg, i. p.) 30 min prior to i. p. injection of SC or LP once daily for 7 days before assessing for memory function utilizing the Y-maze paradigm and levels of biomarkers of oxidative stress using standard biochemical procedures.DP (0.5–2 mg/kg) significantly reversed the memory impairment produced by SC (1 mg/kg) or LP (250 µg/kg) in mice, indicating memory enhancing effect. The increased brain levels of malondialdehyde (MDA) evoked by SC (1 mg/kg) or LP (250 µg/kg), was significantly inhibited by DP (0.5–4 mg/kg), suggesting antioxidant property. Further, DP (0.5–4 mg/kg) significantly inhibited glutathione (GSH) depletion caused by SC (1 mg/kg) or LP (250 µg/kg) in mice brains, which suggest free radical scavenging property.These findings suggest that DP has antioxidant effect, which might be playing a significant role in its memory enhancing activity in mice. However, more detailed studies are necessary to confirm the relevance of this finding and its implications in clinical settings.
Keywords: donepezil; antioxidant; memory function; lipopolysaccharide